Changes in structural and functional retinal features resulting from the effect of a long-acting steroid in serous PED associated with AMD: a 36-month follow-up study - T.B. Kustryn; I.O. Nasinnyk; A.A. Nevskaya; O.S. Zadorozhnyy; A.R. Korol (Ukrainian Society of Ophthalmologists, 2016)
Background: Although a variety of approaches are available for treating retinal pigment epithelial detachment (PED) associated with age-related macular degeneration (AMD), no unified methodology has yet been approved and/or overwhelmingly favored. Purpose: To investigate the effect of a long-acting steroid on the structural and functional RPE features in serous PED associated with AMD in long-term follow-up study, and to improve the efficacy of treatment of this disorder through the use of steroid therapy based on the findings of this investigation. Materials and Methods: Fifty-two patients (54 eyes) with serous PED associated with AMD were followed up for 36 months. They were divided into subtenon and intravitreal groups comprising 30 patients (32 eyes) and 22 patients (22 eyes), respectively, and treated with 0.5 ml (40 mg) subtenon triamcinolone acetonide (TA) suspension and 0.1 ml (4 mg) intravitreal TA crystals, respectively, as needed. Results: We found significant reductions in the height and length of PED in the intravitreal group (from 486 (SD 187) µm to 256 (SD 139) µm, P = 0.005; and from 1859 (SD 911) µm to 1112 (SD 451) µm, P = 0.04, respectively) and in the subtenon group (from 446 (SD 199) µm to 231 (SD 107) µm, P = 0.0001; and from 2055 (SD 587) µm to 1423 (SD 465) µm, P = 0.02, respectively). In study eyes, the visual acuity remained stable throughout the 36-month follow-up period, irrespective of the route of administration of TA. Conclusion: The use of subtenon and intravitreal TA in serous PED associated with AMD is efficacious for maintaining the anatomical structure of the retina.